2019
DOI: 10.1093/advances/nmy037
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Sweeteners on the Gut Microbiota: A Review of Experimental Studies and Clinical Trials

Abstract: The consumption of sugar-free foods is growing because of their low-calorie content and the health concerns about products with high sugar content. Sweeteners that are frequently several hundred thousand times sweeter than sucrose are being consumed as sugar substitutes. Although nonnutritive sweeteners (NNSs) are considered safe and well tolerated, their effects on glucose intolerance, the activation of sweet taste receptors, and alterations to the composition of the intestinal microbiota are controversial. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
285
1
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(307 citation statements)
references
References 95 publications
(133 reference statements)
2
285
1
19
Order By: Relevance
“…Recent studies on the mechanisms by which dietary mono-and disaccharides affect gut microbiota conclude that they tend to increase Bifidobacteria while decreasing Bacteroides. Human subjects' diet with several polyols, including maltitol, lactitol, and isomalt, resulted in increased relative abundance of Bifidobacteria with reduced Bacteroides [71]. In another study, the addition of lactose to the diet resulted in these same bacterial shifts while also decreasing Clostridia species.…”
Section: High Carbohydrate Intake and Intestinal Microbiotamentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies on the mechanisms by which dietary mono-and disaccharides affect gut microbiota conclude that they tend to increase Bifidobacteria while decreasing Bacteroides. Human subjects' diet with several polyols, including maltitol, lactitol, and isomalt, resulted in increased relative abundance of Bifidobacteria with reduced Bacteroides [71]. In another study, the addition of lactose to the diet resulted in these same bacterial shifts while also decreasing Clostridia species.…”
Section: High Carbohydrate Intake and Intestinal Microbiotamentioning
confidence: 90%
“…Many studies reported that a high carbohydrate diet changes the intestinal microbiota, which is associated with metabolic diseases such as type 2 diabetes, cardiovascular disease, and IBD [29,71]. High sugar consumptions induced obesity, insulin resistance, inflammation, and metabolic dysfunction due to changes in the intestinal microbiota in animal studies [56,93].…”
Section: High Carbohydrate Intake and Intestinal Microbiotamentioning
confidence: 99%
“…It has also been proposed that these sweeteners could affect bacteria in the human gut, which are known to play an important role in metabolism, inflammation, immune function and chronic disease . A recent review of experimental studies and clinical trials on the effect of sweeteners on gut microbiota suggested that different types of artificial sweeteners might have different effects on the composition of the gut microbiome, but most of these were animal studies; the authors recommended that further research on the effect of sweeteners on human gut microbiota was needed . In a pooled analysis of the Nurses' Health and Health Professionals' Follow‐up studies, sugar‐sweetened beverage consumption was positively associated with cancer mortality (from all sites) but there was no association for artificially sweetened beverages .…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to confirm and characterize the potentially sex-specific biological mechanisms by which prenatal NNS exposure influences postnatal weight gain and adiposity. In addition to stimulating adipocyte differentiation, NNS may alter the maternal microbiome (33, 34), which is transmitted to the offspring during birth and postnatal interactions (35, 36), and contributes to host metabolism and weight gain (37-39). Future studies should also assess other types and sources of NNS, such as plant-derived NNS and NNS in foods.…”
Section: Discussionmentioning
confidence: 99%